2019
DOI: 10.1021/acsami.8b20703
|View full text |Cite
|
Sign up to set email alerts
|

Ultralong Hydroxyapatite Nanowire-Based Filter Paper for High-Performance Water Purification

Abstract: A new kind of environmentally friendly filter paper based on ultralong hydroxyapatite nanowires (HAPNWs) and cellulose fibers (CFs) with excellent filtration and adsorption properties has been developed for the application in high-performance water purification. The use of polyamidoamine-epichlorohydrin (PAE) resin increases the wet mechanical strength of the as-prepared HAPNW/CF filter paper. The addition of CFs enhances the mechanical strength of the HAPNW/CF filter paper. Owing to the porous structure and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 51 publications
(84 reference statements)
1
35
0
Order By: Relevance
“…A microfiltration filter paper for water purification and wastewater treatment was prepared using ultralong HAP nanowires, plant fibers, and polyamidoamine epichlorohydrin resin. [ 54 ] The polyamidoamine epichlorohydrin resin was adopted as a reinforcement to increase the wet mechanical strength of the filter paper. The large‐sized microfiltration filter paper with a length of 44 cm and a width of 31 cm was also prepared.…”
Section: Applications Of the Fire‐resistant Papermentioning
confidence: 99%
“…A microfiltration filter paper for water purification and wastewater treatment was prepared using ultralong HAP nanowires, plant fibers, and polyamidoamine epichlorohydrin resin. [ 54 ] The polyamidoamine epichlorohydrin resin was adopted as a reinforcement to increase the wet mechanical strength of the filter paper. The large‐sized microfiltration filter paper with a length of 44 cm and a width of 31 cm was also prepared.…”
Section: Applications Of the Fire‐resistant Papermentioning
confidence: 99%
“…The diffusion height was measured from the surface of water or ink upward cessed Xuan paper, the nanocomposite "Xuan paper" with a HAP weight ratio of 25%, and ultralong HAP nanowires. The characteristic bands of PO4 3− ions are located around 1097, 1029, 603 and 561 cm −1 , and the absorption peak at around 3571 cm −1 is derived from the hydroxyl group (−OH) in ultralong HAP nanowires [31][32][33][34] . In addition, the absorption peak at 2920 cm -1 is derived from C−H in cellulose fibers.…”
Section: Preparation Of Bengal Red Medium Containing Sporesmentioning
confidence: 99%
“…Within these areas there it can be found either as a monolith, coatings or as one of the components of composites [ 13 ]. On the other hand, several recent studies have shown the versatility of this material, either in its pure state or combined with other elements in areas completely unrelated to tissue engineering such as: water purification, batteries, drug delivery, catalysis, ion exchange, and sensors [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%